Surface Level Ozone and its Adverse Effects on Crops and Forests: A Need for an Interdisciplinary Understanding - Sagar V. Krupa (The Scientific World Journal)
Surface level ozone (O3) is clearly a global scale problem with regard to its adverse effects on crops, forests and native, terrestrial plant ecosystems. Photochemists and meteorologists are continuing to define the chemistry and physics of the prevalence of O3 at the ground level. Similarly, plant scientists in the U.S. and Europe have examined the effects of O3 on crops and tree seedlings or saplings through large-scale studies. Examples include the U.S. National Crop Loss Assessment Network (NCLAN), the U.S. EPA’s (Environmental Protection Agency’s) San Bernardino National Forest Photochemical Oxidant Study, European Open-top Chambers Programme (EOTCP), and several ongoing EU (European Union) projects. In addition, there have been studies on mature tree responses through field measurements and by simulation modeling.